Digital Transformation of the Kiswah: A Framework for Integrating Additive Manufacturing in Sacred Gold Thread Embroidery - The Case of Al-Kaaba - Madani, Rafat Saleh (Journal of Posthumanism, 2026)
The Kiswah, the black silk cover of the Holy Kaaba in Makkah, is among the most venerated textile artefacts in the Islamic world. Its calligraphic and geometric ornamentation is traditionally executed in a couched gold-thread embroidery technique known as zari, applied over cotton padding to produce the raised thuluth script that protrudes approximately two centimetres from the fabric surface. The annual production of the Kiswah engages approximately 200 to 300 skilled artisans for an eight to twelve-month cycle and consumes between 120 and 200 kilograms of gold and silver thread, at a reported cost in excess of GBP 3.3 million. While the spiritual, cultural, and aesthetic value of this craft is unquestioned, three converging pressures - the deterioration of metallic threads under Makkah’s extreme climatic conditions, the contraction of the traditional craft labour pool, and the sustainability ambitions articulated within Saudi Vision 2030 - have together created a strategic opening to investigate complementary digital production methods. This paper proposes a conceptual framework for integrating additive manufacturing (AM) into the production pipeline of sacred Kiswah ornamentation, while preserving its religious sanctity, traditional aesthetics, and tactile depth. The framework is structured around four interlocking domains: (i) sacred and cultural fidelity, (ii) material and environmental performance, (iii) production economics and sustainability, and (iv) hybrid craft–digital workflows. Each domain is operationalised through a set of performance criteria adapted from the SAFE model (Social, Aesthetic and Affordability, Functionality, Environment) of Almerbati et al. (2014). The framework does not seek to replace artisanal embroidery, but rather to define the conditions under which AM-produced ornamental elements may legitimately complement or substitute for selected components of the traditional process. The paper concludes with a roadmap for empirical validation, identifying material classes (filled photopolymer resins, metal-filled PLA, and technical ceramics) most likely to satisfy the combined sacred, functional, and environmental requirements of the Kiswah.